Implementasi Kepemimpinan Dalam Meningkatakan Mutu Pendidikan Islam di Pondok - Hidayat Rizandi; Izhar Hasan; Demina (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The increasing quality of Islamic educational institutions is strongly influenced by the leadership style applied by those who serve as leaders. Leaders of Islamic educational institutions can use the special characteristics of Islamic leadership in carrying out their responsibilities. The main responsibility for improving the quality of education lies with the leadership of educational institutions. This study aims to apply leadership to improve the quality of Islamic education in Islamic boarding schools. This research covers the types of leadership, the role of leadership in improving the quality of Islamic education, the way leadership is applied by the head of the boarding school, the leadership process, and how leadership is applied to improve the quality of Islamic education in Islamic boarding schools.